Long-Term Dynamics and Features of The Russian Arctic’s Economic Development - Natalia A. SEROVA (Communications of International Proceedings, 2020)
This research aims at studying main trends in the economic development of the Russian Arctic region since 1950-2018. In accordance with the results of this analysis, the author has identified three conceptually different periods in the development of the Russian Arctic zones which involve an intensive economic development stage in 1950-1990; a nascent stage for market relations in 1990-1999; and a modern development stage or a re-development stage for the Russian Arctic region that started in 2000 and has lasted ever since. The paper also demonstrates major features of the Arctic zones’ economic development at each stage.
Keywords: Arctic zone of the Russian Federation; Region; Economic Development.